Kumar & Clark's clinical medicine - Clark, Michael; Kumar, Parveen (Saunders Elsevier, 2009)
Kumar and Clark show the importance of the underpinning sciences in the understanding of clinical medicine and explain clearly the epidemiology, examination, differential diagnosis, investigations and management of disease